[0,1]Truncated Exponentiated Exponential Burr type X Distributionwith Applications - Khalaf, Alaa Abdulrahman; Ibrahim, Mohammed Qasim; Noori , Nooruldeen Ayad; khaleel, Mundher Abdullah (Iraqi Journal of Science, 2024)
We introduce a new flexible distribution four-parameter which is called [0,1]Truncated Exponentiated Exponential Burr type X distribution ([0,1] TEE-BX). Using binomial series expansion and exponential expansion, the new distribution is expanded by four parameters. We derive moments, moment generating function, quantile function, order statistics and the Rényi entropy. The maximum likelihood estimation  method  is used to estimate the parameters of the proposed TEE-BX model [0,1]. Finally, using two real-world data sets, the performance of the [0,1] TEE-BX distribution is explored. Based on the certain goodness of fit criteria, we conclude that the [0,1] TEE-BX distribution has a better fit than the other distributions.